Nickel nanocluster modified porous core-shell complex phase indium oxide material as well as preparation method and application thereof
The porous core-shell complex phase indium oxide material is modified by nickel nanoclusters, which solves the problems of low sensitivity and slow response recovery speed of NO2 sensors, and realizes high sensitivity and fast response NO2 detection, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411325801.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing NO2 sensor has low sensitivity, high detection limit, and slow response recovery speed. It cannot ensure that the gas-sensitive reaction site is in contact with the NO2 molecule quickly, and the reaction activity is poor, requiring high temperature and long response recovery time, resulting in deterioration of gas-sensitive performance.
Nickel nanoclusters are used to modify the porous core-shell complex phase indium oxide material, and the unique porous hollow core-shell morphology structure and the high catalytic activity of nickel nanoclusters promote the diffusion and adsorption of NO2 molecules and inhibit the surface of chemically adsorbed oxygen. Formulate to achieve high sensitivity and rapid response.
Transient NO2 detection in high sensitivity, high selectivity and wide concentration range is achieved at lower operating temperatures, which significantly improves the gas-sensitive reaction activity and response recovery speed of the material and reduces the kinetic barrier.
Smart Images

Figure CN119191341A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas-sensitive materials and relates to a nickel nanocluster-modified porous core-shell composite indium oxide material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Due to nitrogen dioxide (NO 2 ) can cause serious environmental problems and threaten human health, so NO 2 Gas can be detected quickly, quantitatively and accurately. NO 2 The sensor is a resistive semiconductor metal oxide gas sensor. Its working principle is to use the material to exchange electrons with the gas molecules to be measured, causing the energy band of the semiconductor metal oxide material to bend, and the carrier concentration and resistance to change, which then manifests as a response to the gas to be measured. 2 In actual operation, sensors often exhibit problems such as low sensitivity, high detection limit, and slow response recovery. Traditional semiconductor metal oxide sensors cannot ensure that the gas-sensitive reaction sites are closely related to the NO to be detected. 2 Molecules quickly contact, in addition to semiconductor metal oxides and NO 2 The reaction activity is poor, and the thermodynamic barrier required for gas-sensitive reactions is high. 2 Gas-sensitive reactions require higher operating temperatures and longer response recovery times, which in turn leads to the material's sensitivity to NO 2 The gas sensing performance is significantly deteriorated. Summary of the invention
[0004] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a nickel nanocluster modified porous core-shell composite indium oxide material and its preparation method and application. The material provided by the present invention utilizes its unique porous hollow core-shell morphology structure, high NO 2 The catalytic activity and surface dispersion significantly promote NO 2 The diffusion and adsorption process of molecules inhibits the surface formation process of chemically adsorbed oxygen, and successfully achieves transient NO with high sensitivity, high selectivity and wide concentration range at low working temperature. 2 Detection has excellent practical application value and industrial production prospects.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] In the first aspect, a nickel nanocluster modified porous core-shell composite indium oxide material comprises indium oxide and metallic nickel, wherein the molar ratio of indium oxide to metallic nickel is 1:(0-0.2);
[0007] The crystal phase of the indium oxide is a composite phase composed of a cubic phase and a rhombic corundum phase, and the structure of the indium oxide is a porous hollow core-shell micron-spherical structure, which is composed of a shell layer wrapping a core, and a hollow cavity is formed between the shell layer and the core, wherein the shell layer is composed of porous indium oxide nanoparticles, and the core is a micron-sphere assembled from porous indium oxide nanoparticles;
[0008] Metallic nickel is dispersed in the form of nanoclusters on the surface of the porous hollow core-shell micron-spherical structure.
[0009] Indium oxide is an n-type semiconductor with high conductivity and narrow band gap. As the matrix of the composite material, it provides the main gas-sensitive reaction sites. The large number of gaps between nanoparticles and between cores and shells in the porous hollow core-shell micron-spherical structure provide channels for gas diffusion. The core-shell morphology design significantly increases the specific surface area of the material, providing more gas adsorption sites for gas-sensitive reactions. The composite phase formed by the metastable rhombic corundum phase and the stable cubic phase indium oxide has more surface defects and higher chemical activity than the single stable cubic phase indium oxide, which helps to further improve the gas-sensitive reaction activity. Metal nickel is highly evenly dispersed on the surface of the indium oxide material in the form of nanoclusters, which can effectively promote NO 2 Molecular catalysis accelerates NO 2 The gas-sensitive reaction process improves the recovery speed of gas-sensitive response, and the nanocluster size is extremely small, showing a higher surface-to-volume ratio and atomic activity, which can effectively reduce the inhibitory effect of nickel components on the gas adsorption volume, promote the further improvement of nickel catalytic activity, and effectively reduce NO 2 Kinetic barriers of gas-sensing reactions contribute to the realization of transient, highly sensitive, and highly selective NO 2 Detection.
[0010] In some embodiments, the molar ratio of indium oxide to metallic nickel is 1:(0.001-0.2), which can be 1:(0.001-0.1), 1:(0.001-0.05), 1:(0.001-0.02), 1:(0.005-0.2), 1:(0.005-0.1), 1:(0.005-0.05), 1:(0.005-0.02), etc.
[0011] In some embodiments, the porous hollow core-shell microsphere structure has a diameter of 600-700 nm.
[0012] In some embodiments, the shell thickness is 45-55 nm.
[0013] In some embodiments, the core diameter is 350-450 nm.
[0014] In some embodiments, the nickel nanoclusters are 3-7 nm in size.
[0015] In a second aspect, a method for preparing a nickel nanocluster modified porous core-shell composite indium oxide material comprises the following steps:
[0016] Performing a first solvothermal reaction of indium salt and glycerol to obtain an indium glycerate precursor;
[0017] The indium glycerate precursor and the alkaline compound undergo a second solvothermal reaction to obtain an indium glycerate / indium oxyhydroxy precursor;
[0018] The indium glycerate / indium oxyhydroxide precursor is subjected to a first annealing treatment to obtain a porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide;
[0019] The porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and nickel salt are uniformly mixed in a solution, and then the solid and liquid are separated, and the separated solid is subjected to a second annealing treatment under a mixed atmosphere to obtain a mixed atmosphere of an inert atmosphere and a reducing atmosphere.
[0020] The preparation method provided by the present invention can obtain the nickel nanocluster modified porous core-shell composite indium oxide material described in the first aspect of the present invention. Among them, the indium salt provides the required indium ions for the first solvothermal reaction synthesis, and the three hydroxyl groups in glycerol can react with the indium ions to coordinate cross-linking, resulting in the final synthesized precursor product being indium glycerate; the alkaline compound provides an alkaline atmosphere for the second solvothermal reaction, so that indium glycerate and hydroxyl ions react to form an indium oxyhydroxide precursor under closed conditions, prompting the surface components of the indium glycerate precursor to react and diffuse outward and re-form an indium oxyhydroxide shell layer, and the remaining indium glycerate spheres form an inner core; indium oxyhydroxide and indium glycerate will separate during the first annealing process. The metastable rhombic corundum phase indium oxide and the stable cubic phase indium oxide are formed respectively, thereby ensuring the synthesis of porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide; the nickel salt provides nickel ions for material synthesis, which are fully stirred in the solution and exist in the porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide in the form of surface adsorption, and are further annealed into nickel nanoclusters in a reducing atmosphere. The nickel nanoclusters uniformly dispersed on the surface can avoid occupying a large number of active sites of indium oxide, and at the same time form a semiconductor-metal heterogeneous interface between indium oxide and nickel nanoclusters, promote surface interface electron transfer, and provide NO 2 The gas-sensitive reaction provides more reactive free electrons, which helps to improve the gas-sensitive performance.
[0021] The indium salt of the present invention is a compound whose cation is indium ion, such as indium nitrate (In(NO 3 )3 ), indium chloride (InCl 3 ) or indium sulfate (In 2 (SO 4 ) 3 )
[0022] In some embodiments, the molar ratio of indium salt to glycerol is 1:(50-150).
[0023] The solvent thermal reaction described in the present invention is a reaction carried out under closed conditions, using liquid organic matter as a solvent, heating the reaction system to generate high pressure, wherein the "first" and "second" in the first solvent thermal reaction and the second solvent thermal reaction only represent different solvent thermal reaction processes. In some embodiments, the solvent used in the first solvent thermal reaction is isopropanol. The viscosity of the isopropanol solvent is higher than that of deionized water and lower than that of glycerol, which can ensure that the indium ions and glycerol are fully cross-linked and react while increasing the cross-linking reaction rate in the solvent thermal reaction.
[0024] In some embodiments, in the first solvothermal reaction, the reaction temperature is 100-200° C., and the reaction time is 1-12 h.
[0025] The alkaline compound of the present invention is a compound that can make the pH of the aqueous solution greater than 7 when dissolved in water, such as ammonia (NH 3 ·H 2 O), urea (CH 4 N 2 O) or sodium hydroxide (NaOH) or one or more combinations thereof.
[0026] In some embodiments, the solvent used in the second solvothermal reaction is anhydrous ethanol.
[0027] In some embodiments, the molar ratio of the indium glycerate precursor to the basic compound is 1:(50-200).
[0028] In some embodiments, in the second solvothermal reaction, the reaction temperature is 100-200° C., and the reaction time is 1-12 h.
[0029] In some embodiments, the first annealing treatment is performed at a temperature of 400-600° C. and for a time of 1-3 hours.
[0030] In some embodiments, the porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide is dispersed into a solution, and then nickel salt is added and stirred sufficiently to make the porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and nickel salt uniformly mixed in the solution. Specifically, the solution is anhydrous ethanol.
[0031] The nickel salt described in the present invention is a compound in which the cation is a nickel ion, such as nickel nitrate (Ni(NO3 ) 2 ), nickel chloride (NiCl 2 ) or nickel acetate (Ni(CH 3 COO 2 )
[0032] In some embodiments, the molar ratio of porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide to nickel salt is 1:(0-0.02), which can be 1:(0.001-0.2), 1:(0.001-0.1), 1:(0.001-0.05), 1:(0.001-0.02), 1:(0.005-0.2), 1:(0.005-0.1), 1:(0.005-0.05), 1:(0.005-0.02), etc.
[0033] In some embodiments, the volume fraction of the reducing atmosphere in the mixed atmosphere is 8-12%. The reducing atmosphere can be formed by reducing gases such as hydrogen. The inert atmosphere can be formed by gases such as nitrogen, helium, argon, and xenon. During the second annealing treatment, the mixed gas is continuously introduced into the reaction system, and the flow rate of the mixed gas is 50-150 mL / min.
[0034] In some embodiments, the second annealing treatment is performed at a temperature of 100-300° C. and a time of 1-6 hours.
[0035] In a third aspect, a gas-sensitive element comprises a ceramic substrate and a gas-sensitive material, wherein the gas-sensitive material forms a sensing layer on the ceramic substrate, and the gas-sensitive material is the above-mentioned nickel nanocluster-modified porous core-shell composite indium oxide material.
[0036] The preparation method of the gas sensor is as follows: the gas sensitive material is mixed with deionized water and then ground evenly to form a slurry, the obtained slurry is evenly coated on a ceramic substrate, and then dried, and the coating and drying process is repeated several times, and then the slurry is completely dried.
[0037] In some embodiments, the mass ratio of the nickel nanocluster modified porous hollow core-shell heterogeneous indium oxide composite material to deionized water is 1:(2-6).
[0038] In some embodiments, the drying temperature of the ceramic substrate is 70-100° C., and the drying time is 2-6 min.
[0039] In some embodiments, the thorough drying temperature is 80-120° C. and the drying time is 8-24 h.
[0040] In a fourth aspect, a nickel nanocluster modified porous core-shell composite indium oxide material or a gas sensor is used to detect NO 2 Application in.
[0041] The beneficial effects of the present invention are:
[0042] (1) The nickel nanocluster modified porous hollow core-shell composite indium oxide composite material prepared by the present invention, the porous hollow core-shell cubic phase / rhombic corundum composite indium oxide is a micron-spherical morphology, composed of a nanoparticle assembled shell layer and a nanoparticle assembled micron-spherical core body, the unique porous hollow core-shell structure design significantly increases the specific surface area of the material, and provides abundant gas-sensitive reaction sites; the gaps between the porous nanoparticles and the core-shell layer are NO 2 It provides a large number of diffusion channels, which can effectively improve the gas sensitivity and response recovery speed of the material.
[0043] (2) The nickel nanocluster modified porous hollow core-shell multiphase indium oxide composite material prepared by the present invention is prepared by regulating the solvothermal reaction of indium glycerate / indium oxyhydroxide precursor, and the porous hollow core-shell microsphere morphology is constructed while realizing the synthesis of a stable cubic phase / metastable rhombic corundum phase multiphase indium oxide matrix material. Compared with the stable cubic phase indium oxide, the metastable rhombic corundum phase indium oxide has more surface defects and higher chemical activity, which effectively increases the defect concentration of the matrix material and promotes NO 2 Adsorption and reaction to optimize material NO 2 Gas sensitive response capability.
[0044] (3) Compared with the traditional bulk / body nickel materials, the nickel nanoclusters modified porous hollow core-shell composite indium oxide prepared by the present invention have extremely small sizes of nickel nanoclusters modified on the surface of indium oxide, showing higher surface-to-volume ratio and atomic activity, which can effectively reduce the inhibitory effect of nickel components on gas adsorption volume, and at the same time show excellent catalytic conversion of NO 2 Molecular properties, can effectively reduce NO 2 Kinetic barriers of gas-sensing reactions contribute to the realization of transient, highly sensitive, and highly selective NO 2 Detection.
[0045] (4) The nickel nanocluster modified porous hollow core-shell composite indium oxide prepared by the present invention has good performance in the treatment of NO 2 The detection showed a transient response recovery speed (1 / 3s), excellent NO 2 Response characteristics, 10ppm NO at 200℃ 2 The response value can reach 454.62 for NO 2 The detection limit of NO 2 It can still show excellent selectivity in the detection of NO, which can effectively avoid the 2 The detection is affected by other interfering gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0047] Figure 1 The XRD patterns of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1-9 of the present invention; wherein, a is the XRD pattern of the cubic indium oxide and porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide materials prepared in Examples 1-5; b is the XRD pattern of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, 6-9.
[0048] Figure 2 The present invention provides SEM images of porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 6-9; wherein, a is a SEM image of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material prepared in Example 4; b is a SEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 6; c is a SEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7; d is a SEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 8; e is a SEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 9.
[0049] Figure 3TEM, HRTEM and HAADF-STEM spectra of cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7 of the present invention; wherein a and b are TEM images of cubic indium oxide prepared in Example 1, and the inset in b is a selected area electron diffraction image; c is an HRTEM image of cubic indium oxide prepared in Example 1; d and e are regional images of measuring interplanar spacing values in c; f and g are TEM images of porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide prepared in Example 4, and the inset in g is a selected area electron diffraction image; h is a porous hollow core-shell prepared in Example 4. HRTEM image of cubic phase / rhombic corundum multiphase indium oxide; i and j are the regional diagrams of the measured interplanar spacing values in h; k and l are TEM images of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7, and the inset in l is the selected area electron diffraction image; m is the HRTEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7; n, o, p are the regional diagrams of the measured interplanar spacing values in m; q is the HAADF-STEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7; r, s, t are the surface distribution maps of In, Ni and O elements respectively.
[0050] Figure 4 XPS spectra of cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide, and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, 6-9 of the present invention; wherein a is In3 d is a fine spectrum; b is an O1s fine spectrum of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, 6-9; c is a Ni2p fine spectrum of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 7, 9.
[0051] Figure 5The BET-BJH spectra and specific surface area-pore volume distribution of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites prepared in Examples 1, 4 and 7 of the present invention; wherein a is the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites prepared in Examples 1, 4 and 7. a is the BET spectrum of the material; b is the BJH spectrum of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7; c is the specific surface area-pore volume distribution of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7.
[0052] Figure 6 The cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Examples 1, 4 and 7 of the present invention are prepared in the following manner: 2 -TPD spectrum.
[0053] Figure 7 The porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites prepared in Examples 4, 6-9 of the present invention were subjected to 10 ppm NO at different working temperatures. 2 The response value changes.
[0054] Figure 8 The porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 6-9 of the present invention were subjected to 10 ppm NO at 200 °C. 2 And the response value of other interfering gases at 100ppm.
[0055] Fig. 9 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention was subjected to 20-0.001 ppm NO at 200°C. 2 Response recovery curve; wherein a is the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 at 200 ° C for 20-0.001ppm NO 2b is the response recovery curve of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 at 200 ° C for 0.1-0.001ppm NO 2 Response recovery curve.
[0056] Fig.10 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention was subjected to 10 ppm NO at 200 °C. 2 Response recovery curve of
[0057] Fig.11 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention was subjected to 10 ppm NO at 200 °C. 2 Response recovery cycle curve;
[0058] Fig.12 Schematic diagram of finite element simulation of cubic indium oxide and porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide materials prepared in Examples 1 and 4 of the present invention; wherein a is 10 ppm NO on the surface of cubic indium oxide prepared in Example 1 2 NO after 5s of constant source diffusion 2 Spatial concentration distribution diagram; b is the porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide surface 10ppm NO prepared in Example 4 2 NO after 5s of constant source diffusion 2 Spatial concentration distribution map.
[0059] Fig.13 This is a schematic diagram of the gas sensor prepared in Example 10 of the present invention. DETAILED DESCRIPTION
[0060] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0061] Example 1
[0062] A method for preparing a cubic indium oxide material comprises the following steps:
[0063] WillIn(NO 3 ) 3 , glycerol was dissolved in 30 mL of isopropanol at a molar ratio of 1:135, mixed evenly, and then solvent-thermally reacted at 180°C for 1 hour under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0064] The prepared indium glycerate precursor was annealed at 400° C. for 1 h to obtain a cubic indium oxide material.
[0065] Example 2
[0066] A method for preparing a porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material comprises the following steps:
[0067] InCl 3 , glycerol was dissolved in 60 mL of isopropanol at a molar ratio of 1:50, mixed evenly, and then solvent-thermally reacted at 100°C for 12 h under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0068] The prepared indium glycerate precursor was dissolved in 10 mL of anhydrous ethanol and evenly dispersed, and NH 2 O was added to the solution at a molar ratio of 1:100 to the indium glycerate precursor. 3 ·H 2 O, after being uniformly dissolved, the solution was transferred to a closed condition, and the solvent thermal reaction was carried out at 160°C for 1 hour. The reaction product was centrifuged, washed and dried to obtain an indium glycerate / indium oxyhydroxide precursor;
[0069] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 600° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide material.
[0070] Example 3
[0071] A method for preparing a porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material comprises the following steps:
[0072] In 2 (SO 4 ) 3 , glycerol was dissolved in 45 mL of isopropanol at a molar ratio of 1:150, mixed evenly, and then solvent-thermally reacted at 120°C for 4 hours under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0073] The prepared indium glycerate precursor was dissolved in 30 mL of anhydrous ethanol and evenly dispersed. CH 4 N 2 O, after being uniformly dissolved, the solution was transferred to a closed condition, and the solvent thermal reaction was carried out at 200°C for 12 hours. The reaction product was centrifuged, washed and dried to obtain an indium glycerate / indium oxyhydroxide precursor;
[0074] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 450° C. for 3 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0075] Example 4
[0076] A method for preparing a porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material comprises the following steps:
[0077] WillIn(NO 3 ) 3 , glycerol was dissolved in 50 mL of isopropanol at a molar ratio of 1:120, mixed evenly, and then solvent-thermally reacted at 160°C for 6 hours under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0078] The prepared indium glycerate precursor was dissolved in 40 mL of anhydrous ethanol and uniformly dispersed, and NaOH was added to the solution at a molar ratio of 1:130 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 180°C for 3 hours. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0079] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 500° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0080] Example 5
[0081] A method for preparing a porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material comprises the following steps:
[0082] WillIn(NO 3 ) 3 , glycerol was dissolved in 30 mL of isopropanol at a molar ratio of 1:160, mixed evenly, and then solvent-thermally reacted at 120°C for 8 h under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0083] The prepared indium glycerate precursor was dissolved in 50 mL of anhydrous ethanol and evenly dispersed. CH 4 N 2 O, after being uniformly dissolved, the solution was transferred to a closed condition, and the solvent thermal reaction was carried out at 120°C for 12 hours, and the reaction product was centrifuged, washed and dried to obtain an indium glycerate / indium oxyhydroxide precursor;
[0084] The prepared indium glycerate / indium hydroxide oxide precursor was annealed at 550° C. for 2 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0085] Example 6
[0086] A method for preparing a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material comprises the following steps:
[0087] InCl3 , glycerol was dissolved in 45 mL of isopropanol at a molar ratio of 1:110, mixed evenly, and then solvent-thermally reacted at 100°C for 8 hours under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0088] The prepared indium glycerate precursor was dissolved in 30 mL of anhydrous ethanol and uniformly dispersed, and NaOH was added to the solution at a molar ratio of 1:160 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 130° C. for 6 h. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0089] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 450° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0090] The prepared porous hollow core-shell cubic phase / rhombic corundum composite indium oxide was dissolved in 30 mL of anhydrous ethanol solution and stirred thoroughly until uniformly dispersed. Then Ni(NO 3 ) 2 After being fully stirred, the sample was centrifuged, washed and dried, and then subjected to 10% H 2 / 90%N 2 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material was obtained by annealing at 100°C for 1 h in a mixed gas.
[0091] Example 7
[0092] A method for preparing a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material comprises the following steps:
[0093] In 2 (SO 4 ) 3 , glycerol was dissolved in 60 mL of isopropanol at a molar ratio of 1:60, mixed evenly, and then solvent-thermally reacted at 190° C. for 12 h under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0094] The prepared indium glycerate precursor was dissolved in 50 mL of anhydrous ethanol and evenly dispersed. CH 4 N 2 O, after being uniformly dissolved, the solution was transferred to a closed condition, and the solvent thermal reaction was carried out at 100°C for 12 hours. The reaction product was centrifuged, washed and dried to obtain an indium glycerate / indium oxyhydroxide precursor;
[0095] The prepared indium glycerate / indium hydroxide oxide precursor was annealed at 600° C. for 2.5 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0096] The prepared porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide was dissolved in 35 mL of anhydrous ethanol solution and stirred thoroughly until uniformly dispersed. Then Ni(NO 3 ) 2 After being fully stirred, the sample was centrifuged, washed and dried, and then subjected to 10% H 2 / 90%N 2 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material was obtained by annealing at 200°C for 2h in a mixed gas.
[0097] Example 8
[0098] A method for preparing a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material comprises the following steps:
[0099] WillIn(NO 3 ) 3 , glycerol was dissolved in 30 mL of isopropanol at a molar ratio of 1:50, mixed evenly, and then solvent-thermally reacted at 160°C for 2 h under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0100] The prepared indium glycerate precursor was dissolved in 40 mL of anhydrous ethanol and evenly dispersed, and NH 3 ·H 2 O, after being uniformly dissolved, the solution was transferred to a closed condition, and the solvent thermal reaction was carried out at 200°C for 1 hour. The reaction product was centrifuged, washed and dried to obtain an indium glycerate / indium oxyhydroxide precursor;
[0101] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 550° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0102] The prepared porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide was dissolved in 60 mL of anhydrous ethanol solution and stirred thoroughly until uniformly dispersed. Then Ni(CH 3 COO 2 After being fully stirred, the sample was centrifuged, washed and dried, and then the sample was subjected to 10% H 2 / 90%N 2The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material was obtained by annealing at 180°C for 3h in a mixed gas.
[0103] Example 9
[0104] A method for preparing a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material comprises the following steps:
[0105] InCl 3 , glycerol was dissolved in 60 mL of isopropanol at a molar ratio of 1:150, mixed evenly, and then solvent-thermally reacted at 200°C for 4 hours under closed conditions, and the reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor;
[0106] The prepared indium glycerate precursor was dissolved in 55 mL of anhydrous ethanol and evenly dispersed. CH 4 N 2 O, after being uniformly dissolved, the solution was transferred to a closed condition, and the solvent thermal reaction was carried out at 140°C for 12 hours. The reaction product was centrifuged, washed and dried to obtain an indium glycerate / indium oxyhydroxide precursor;
[0107] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 600° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide material.
[0108] The prepared porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide was dissolved in 50 mL of anhydrous ethanol solution and stirred thoroughly until uniformly dispersed. NiCl was added to the solution at a molar ratio of 1:0.02. 2 After being fully stirred, the sample was centrifuged, washed and dried, and then subjected to 10% H 2 / 90%N 2 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material was obtained by annealing at 300°C for 1h in a mixed gas.
[0109] Example 10
[0110] A gas sensor and a preparation method thereof, the gas sensor comprising a ceramic substrate, a platinum wire, a gas sensing material and a gold electrode, the preparation method specifically comprising the following steps:
[0111] The cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide composite materials prepared in Examples 1-9 were mixed with deionized water in a mass ratio of 1:5 and ground evenly to form a slurry. The resulting slurry was then evenly coated on a ceramic substrate, and the ceramic substrate was placed in an oven at 80°C and dried for 5 minutes before being taken out. After repeating the coating and drying process five times, the ceramic substrate coated with the gas-sensitive material was placed in an oven at 100°C and dried for 12 hours, and a platinum wire was connected to obtain a gas-sensitive element.
[0112] Performance Test:
[0113] Figure 1 The cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1-9 of the present invention; Figure 1 It can be obtained that the material prepared in Example 1 exhibits a pure cubic phase structure, proving that the indium glycerate precursor can be completely transformed into cubic indium oxide after annealing, and the indium glycerate precursor can obtain a cubic phase / rhombic corundum multiphase indium oxide material after further solvent thermal reaction and annealing under alkaline conditions, and the diffraction peak intensity related to the rhombic corundum phase will increase with the increase of the alkali source concentration; from Figure 1 It can be observed in b that the nickel nanoclusters modified on the surface of the cubic phase / rhombic corundum complex phase indium oxide material will not destroy the original cubic phase / rhombic corundum complex phase crystal structure; no obvious nickel-related diffraction peaks were observed in the XRD spectra of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide composite materials prepared in Examples 6-9, proving that the nickel content is low and highly dispersed on the surface of the cubic phase / rhombic corundum complex phase indium oxide composite materials.
[0114] Figure 2 The SEM images of the porous hollow core-shell cubic phase / rhombic corundum complex indium oxide and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex indium oxide composite materials prepared in Examples 4 and 6-9 of the present invention; it can be seen that the porous hollow core-shell cubic phase / rhombic corundum complex indium oxide and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex indium oxide composite materials prepared in Examples 4 and 6-9 all exhibit typical micron-spherical structures, with a diameter of about 600 nm, and the micron-spheres are further formed by the accumulation of a large number of nanoparticles. At the same time, no obvious nickel-related structures are observed on the surface, which proves that the nickel nanoclusters are highly dispersedly grown on the surface of the cubic phase / rhombic corundum complex indium oxide matrix.
[0115] Figure 3TEM, HRTEM and HAADF-STEM spectra of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7 of the present invention; Figure 3 a and Figure 3 In b, it can be observed that the cubic indium oxide material has a micron-spherical morphology with a diameter of about 600nm, and is further composed of nanoparticles. The characteristic diffraction rings of cubic indium oxide are calibrated in the selected area electron diffraction. In addition, Figure 3 The interplanar spacings marked in regions d and e in c correspond to the (211) and (222) planes of cubic indium oxide, respectively, proving that the synthesized material is cubic indium oxide. Figure 3 f and Figure 3 g, it can be observed that the cubic phase / rhombic corundum multiphase indium oxide composite material exhibits a porous hollow core-shell microsphere morphology, in which the outer sphere diameter is about 660nm, the shell thickness is about 50nm, the inner sphere core diameter is about 400nm, and it is further stacked by nanoparticles. The characteristic diffraction rings of cubic phase indium oxide and rhombic corundum phase indium oxide are calibrated in the selected area electron diffraction. In addition, Figure 3 The interplanar spacings marked in regions i and j in h correspond to the (400) crystal plane of cubic indium oxide and the (104) crystal plane of rhombic corundum phase indium oxide, respectively, proving that the synthesized material is a cubic phase / rhombic corundum multiphase indium oxide composite material. Figure 3 k and Figure 3 It can be observed in Figure 1 that the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material still exhibits a porous hollow core-shell microsphere morphology, in which the outer sphere diameter, sphere shell thickness, and inner sphere core diameter are close to those of the cubic phase / rhombic corundum multiphase indium oxide composite material, and are further stacked by nanoparticles. The characteristic diffraction rings of cubic phase indium oxide and rhombic corundum phase indium oxide and the diffraction spots of nickel are simultaneously calibrated in the selected area electron diffraction. In addition, Figure 3 The interplanar spacings marked in the n, o, and p regions in m correspond to the (211) crystal plane of cubic indium oxide, the (110) crystal plane of rhombic corundum phase indium oxide, and the (012) crystal plane of nickel, respectively, proving that the synthesized material is a nickel nanocluster-modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material. Figure 3 The HAADF-STEM image and element distribution diagram of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material modified by nickel nanoclusters in qt show the uniform distribution of In, O, and Ni, proving that the prepared material contains the above elements, among which the Ni signal is weak and evenly distributed, proving that the nickel nanoclusters are highly evenly dispersed and loaded on the surface of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material.
[0116] Figure 4 XPS spectra of cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide, and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, 6-9 of the present invention; wherein, from Figure 4 It can be seen from a that the In ions in the sample all appear in the valence states of +2 and +3. The generation of +2-valence In ions indicates that the synthesized material contains a large number of positively charged structural defects, and the material structure compensates for the electrical neutrality and causes the In ions to transform to a low-valence state. Figure 4 As can be seen from b, all samples contain adsorbed oxygen, oxygen vacancies and lattice oxygen components. After surface nickel nanoclusters are modified, the lattice oxygen component in the material increases significantly while the proportion of chemically adsorbed oxygen decreases significantly, proving that nickel nanoclusters can inhibit the generation of surface chemically adsorbed oxygen. 2 Both exhibit electron-withdrawing properties. A high content of chemically adsorbed oxygen on the surface of the material consumes more free electrons, thereby inhibiting NO 2 The ability to react with free electrons in the conduction band of the material further inhibits the material from reacting with NO 2 The sensitivity of Ni nanoclusters is that the modification of Ni nanoclusters promotes the 2 Gas-sensitive reaction with materials; Figure 4 c It can be seen that there is no Ni signal in the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide prepared in Example 4, and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 shows Ni 3+ The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 4 showed signals of both metallic Ni and Ni-Ni bonds, proving that excessive addition of nickel source will cause spontaneous agglomeration of nickel nanoclusters, thereby inhibiting its surface-to-volume ratio and chemical activity, and further inhibiting its gas-sensing performance.
[0117] Figure 5 The BET-BJH spectra and specific surface area-pore volume distribution of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7 of the present invention; the specific surface areas of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials are calculated to be 35.46, 65.58 and 54.03 m 2 g -1 , the pore volumes are 0.00575, 0.01158 and 0.01175 cm3 g -1 nm -1 It shows that the porous hollow core-shell cubic phase / rhombic corundum composite indium oxide morphology construction will significantly increase the specific surface area and porosity of the material, increase the number of gas-sensitive reaction sites and gas diffusion channels, and promote NO 2 The sensitivity of gas-sensitive reactions and the response recovery speed are improved; and the nickel nanocluster modification will not have a significant effect on the specific surface area and porosity of the material, that is, the nickel nanocluster modification will not significantly inhibit the gas-sensitive performance.
[0118] Figure 6 The cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Examples 1, 4 and 7 of the present invention are prepared in the following manner: 2 -TPD spectrum. It can be clearly seen that the NO 2 The desorption peak intensity is the highest, while the cubic indium oxide intensity is the lowest, indicating that the morphology and phase structure design of the porous hollow core-shell cubic phase / rhombic corundum composite indium oxide and the surface modification of nickel nanoclusters will promote NO 2 The adsorption of NO was significantly increased by nickel nanoclusters. 2 The adsorption amount of nickel nanoclusters modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material can show better NO 2 Gas sensitive response capability.
[0119] Figure 7 The porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites prepared in Examples 4, 6-9 of the present invention were subjected to 10 ppm NO at different working temperatures. 2 It can be seen that the samples all showed the best NO response at 200 °C. 2 Response value, NO of nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites 2 The response values are higher than those of porous hollow core-shell cubic phase / rhombic corundum composite indium oxide, proving that nickel nanoclusters can effectively improve the material's NO 2 In addition, the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 can reach a response value of 454.92 to 10 ppm, showing excellent NO 2 Gas sensing performance.
[0120] Figure 8The porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 6-9 of the present invention were subjected to 10 ppm NO at 200 °C. 2 And the response values of other interfering gases at 100ppm. It can be seen that the material is very sensitive to NO 2 The sensitivity of the composite materials is much higher than that of other interfering gases, which proves that the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials both exhibit excellent NO 2 Gas sensitive selectivity.
[0121] Fig. 9 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention was subjected to 20-0.001 ppm NO at 200°C. 2 The response recovery curve of nickel nanoclusters modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material is 2 All of them showed obvious response values and fast response recovery speed, proving that nickel nanoclusters modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials can achieve a wide range of NO concentrations. 2 Quantitative, rapid and high-precision detection.
[0122] Fig.10 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention was subjected to 10 ppm NO at 200 °C. 2 The response recovery curve shows that the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material has a strong effect on 10 ppm NO 2 The excellent sensitivity was shown, with the recorded response and recovery times of 1 s and 3 s, respectively, indicating that nickel nanoclusters modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites can achieve NO 2 Highly sensitive transient detection of gases.
[0123] Fig.11 The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention was subjected to 10 ppm NO at 200 °C. 2 The response recovery cycle curve shows that in five consecutive tests, the response value and response recovery speed of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material are almost unaffected by the ambient humidity. The material can complete 10 consecutive complete NO reactions within 600 s. 2The response recovery process proves that nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites have fast, stable and precise NO 2 Gas identification capability.
[0124] Fig.12 Schematic diagram of finite element simulation of cubic indium oxide and porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide materials prepared in Examples 1 and 4 of the present invention, according to Figure 2 , Figure 3 , Figure 5 The finite element model was constructed based on the results in the paper. A 10 ppm constant source concentration field was applied to the outer surface of the model, and the NO concentration was recorded 5 seconds after the diffusion process started. 2 The spatial concentration distribution shows that for cubic indium oxide, due to its lower specific surface area and porosity, NO 2 It is difficult for the gas to diffuse quickly into the microsphere structure, so the concentration in the inner area is low. For the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material, the finite element simulation results show that the NO in the hollow structure of the porous hollow core-shell layer 2 The high concentration indicates that its unique porous hollow core-shell structure design can effectively promote NO 2 The molecules diffuse into the material, promoting more NO 2 The molecules quickly contact the gas-sensitive reaction sites, thereby achieving the material's NO 2 The comprehensive gas sensing performance of response value and response recovery speed is improved.
[0125] Fig.13 The schematic diagram of the gas sensor prepared in Example 10 of the present invention includes a ceramic substrate, a gold electrode, four platinum wires and a sensing material. In the preparation process of the gas sensor, the prepared gas-sensitive material is coated on the ceramic substrate, and after uniform coating and drying, the ceramic substrate is welded to the four corner bases through four platinum wires to obtain the gas sensor.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A nickel nanocluster modified porous core-shell composite indium oxide material, characterized in that: Comprising indium oxide and metallic nickel, wherein the molar ratio of indium oxide to metallic nickel is 1:(0-0.2); The crystal phase of the indium oxide is a composite phase composed of a cubic phase and a rhombic corundum phase, and the structure of the indium oxide is a porous hollow core-shell micron-spherical structure, which is composed of a shell layer wrapping a core, and a hollow cavity is formed between the shell layer and the core, wherein the shell layer is composed of porous indium oxide nanoparticles, and the core is a micron-sphere assembled from porous indium oxide nanoparticles; Metallic nickel is dispersed in the form of nanoclusters on the surface of the porous hollow core-shell micron-spherical structure.
2. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 1, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.001-0.2); preferably 1:(0.001-0.1), 1:(0.001-0.05), 1:(0.001-0.02), 1:(0.005-0.2), 1:(0.005-0.1), 1:(0.005-0.05), 1:(0.005-0.02).
3. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 1, characterized in that: The diameter of the porous hollow core-shell microsphere structure is 600-700nm; or, shell thickness is 45-55 nm; or, core diameter is 350-450nm; Alternatively, the size of nickel nanoclusters is 3-7 nm.
4. A method for preparing a nickel nanocluster modified porous core-shell composite indium oxide material, characterized in that: The steps include: Performing a first solvothermal reaction of indium salt and glycerol to obtain an indium glycerate precursor; The indium glycerate precursor and the alkaline compound undergo a second solvothermal reaction to obtain an indium glycerate / indium oxyhydroxy precursor; The indium glycerate / indium oxyhydroxide precursor is subjected to a first annealing treatment to obtain a porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide; The porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and nickel salt are uniformly mixed in a solution, and then the solid and liquid are separated, and the separated solid is subjected to a second annealing treatment under a mixed atmosphere to obtain a mixed atmosphere of an inert atmosphere and a reducing atmosphere.
5. The preparation method according to claim 4, characterized in that: The molar ratio of indium salt to propylene glycol is 1:(50-150); Or, the solvent used in the first solvothermal reaction is isopropanol; Alternatively, in the first solvothermal reaction, the reaction temperature is 100-200° C., and the reaction time is 1-12 h.
6. The preparation method according to claim 4, characterized in that: The solvent used in the second solvothermal reaction is anhydrous ethanol; Or, the molar ratio of the indium glycerate precursor to the alkaline compound is 1:(50-200); Or, in the second solvothermal reaction, the reaction temperature is 100-200° C., and the reaction time is 1-12 h; Alternatively, the temperature of the first annealing treatment is 400-600° C., and the annealing time is 1-3 hours.
7. The preparation method according to claim 4, characterized in that: Dispersing the porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide into the solution, then adding nickel salt, and stirring thoroughly to make the porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide and the nickel salt evenly mixed in the solution; Or, the molar ratio of porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide to nickel salt is 1:(0-0.02); preferably 1:(0.001-0.2), 1:(0.001-0.1), 1:(0.001-0.05), 1:(0.001-0.02), 1:(0.005-0.2), 1:(0.005-0.1), 1:(0.005-0.05), 1:(0.005-0.02).
8. The preparation method according to claim 4, characterized in that: In the mixed atmosphere, the volume fraction of reducing atmosphere is 8-12%; Alternatively, the second annealing treatment is performed at a temperature of 100-300° C. and a annealing time of 1-6 hours.
9. A gas sensor, comprising a ceramic substrate and a gas-sensitive material, wherein the gas-sensitive material forms a sensing layer on the ceramic substrate, wherein: The gas-sensitive material is the nickel nanocluster-modified porous core-shell composite indium oxide material described in any one of claims 1 to 3 or the nickel nanocluster-modified porous core-shell composite indium oxide material obtained by the preparation method described in any one of claims 4 to 8.
10. Use of the nickel nanocluster modified porous core-shell complex indium oxide material described in any one of claims 1 to 3, or the nickel nanocluster modified porous core-shell complex indium oxide material obtained by the preparation method described in any one of claims 4 to 8, or the gas sensor described in claim 9 in detecting NO2.
Citation Information
Patent Citations
Reduced graphene oxide coated platinum / stannic oxide nano-particle cluster gas sensor and preparation method thereof
CN108318510A
Gas sensor based on p-n heterojunction structure NiO-In2O3 composite nanosphere
CN109632893A
Alkaline system direct urea fuel cell anode catalyst and preparation method thereof
CN116470077A
Nanostructured metal oxides and mixed metal oxides, methods of making these nanoparticles, and methods of their use
US20130089739A1
Universal precursor for nanoscale morphologies
US20230033797A1
